Pengabdian mahasiswa UNIKA Medan kepada masyarakat melalui Kuliah Kerja Nyata (KKN) di Desa Tanjung Beringin I, Kacamatan Sumbul, Kabupaten Dairi - Anggun Rosittauli Br Gurning; Dewi Clara Damanik; Trivani P Sihaloho; Elva Septiani Br Siburian; Marlince Naibaho; Iyo Karsella Br Sembiring; Febriany Tampubolon; Lasro Tua Hutasoit; Fiber Yun Almanda Ginting (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2025)
The form of community service carried out by students is real work lectures (KKN). In an effort to educate the nation, one of the activities that needs to be carried out by KKN students is activities in the field of education. For this reason, counseling activities are carried out with the aim that KKN students are able to compile community service activity programs in the educational aspect. Counseling activities carried out by field supervisors and lecturers at UNIKA Medan to KKN students in Tanjung Beringin I Village, Sumbul District, Dairi Regency with the title "UNIKA Medan student service to the community through Real Work Lectures (KKN) in Tanjung Beringin I Village, Sumbul District, Dairi Regency". This activity can be carried out well and produces several KKN student activity programs in the field of Education, namely teaching Indonesian language lessons, English lessons, Mathematics lessons, reactivating religious studies, and helping teachers teach at PAUD. This activity targets elementary school students which also involves parents, teachers, village government, and village communities in Tanjung Beringin I Village, Sumbul District, Dairi Regency